Analisis makro kinerja pasar modal Indonesia dengan pendekatan Error Correction Model (ECM) - Rini Dwi Astuti (Economic Journal of Emerging Markets, 2016)
In Indonesia, monetary crisis had brought economy damage, particularly at the capital market. This study, concerns with analysis of capital market conducted in macro economy perspective and using Error Correction Model (ECM) Approach. How did foreign exchange fluctuation, deposit at banking sector, real deposit rate, LIBOR, and monetary crisis since August 1997, influence on the capital market performance?